Mobile technology to monitor depression symptoms of the elderly worker: an experience report - Barbosa, Maria do Socorro Alécio; Nascimento, Kelly Cristina do; Oliveira, Thais da Silva; Lima, Tereza Natália Bezerra de; Tertuliano, Ana Karla; Lima, Fabia Maria de (JRG Journal of Academic Studies, 2023)
This is a descriptive study of an experience report with a theoretical-practical approach, which forms part of the doctoral thesis of one of the authors, carried out as part of a joint programme between the University of Pernambuco and the State University of Paraíba. The knowledge gained from this experience encourages the researchers to continue along this path and face new challenges in favour of the health of the elderly workers of the future. In addition, it opens up a range of possibilities for nursing, even though it does not have specific training in technology. However, the willingness and openness to new ways of caring were fundamental, even though they had to face new situations, such as the lack of training in the use of information and communication technologies, the objective was achieved.